2019
DOI: 10.7554/elife.47163
|View full text |Cite
|
Sign up to set email alerts
|

Defined neuronal populations drive fatal phenotype in a mouse model of Leigh syndrome

Abstract: Mitochondrial deficits in energy production cause untreatable and fatal pathologies known as mitochondrial disease (MD). Central nervous system affectation is critical in Leigh Syndrome (LS), a common MD presentation, leading to motor and respiratory deficits, seizures and premature death. However, only specific neuronal populations are affected. Furthermore, their molecular identity and their contribution to the disease remains unknown. Here, using a mouse model of LS lacking the mitochondrial complex I subun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 70 publications
2
70
0
Order By: Relevance
“…Having demonstrated the high degree of specificity for Vglut2-driven Cre expression in RGCs histologically, we proceeded to establish a Vglut2-Cre;ndufs4 loxP/loxP transgenic mouse line in order to achieve RGC-specific deletion of ndufs4. The systemic phenotype of ndufs4 deletion in Vglut2-expressing glutamatergic neurons was recently described by another group which independently generated Vglut2-Cre;ndufs4 loxP/loxP transgenic mice but did not characterize the retinal phenotype 29 . Consistent with their report, we observed that Vglut2-Cre;ndufs4 loxP/loxP mice are initially healthy but develop progressive weight loss, ataxia, and hindlimb weakness beginning around P60.…”
Section: Rgc Somas and Axons Undergo Progressive Degeneration In Vglumentioning
confidence: 96%
“…Having demonstrated the high degree of specificity for Vglut2-driven Cre expression in RGCs histologically, we proceeded to establish a Vglut2-Cre;ndufs4 loxP/loxP transgenic mouse line in order to achieve RGC-specific deletion of ndufs4. The systemic phenotype of ndufs4 deletion in Vglut2-expressing glutamatergic neurons was recently described by another group which independently generated Vglut2-Cre;ndufs4 loxP/loxP transgenic mice but did not characterize the retinal phenotype 29 . Consistent with their report, we observed that Vglut2-Cre;ndufs4 loxP/loxP mice are initially healthy but develop progressive weight loss, ataxia, and hindlimb weakness beginning around P60.…”
Section: Rgc Somas and Axons Undergo Progressive Degeneration In Vglumentioning
confidence: 96%
“…Avoid installing the equipment in unstable surfaces or close to high-traffic areas.3. Close the chamber tightly and make sure the animal moves freely 4…”
mentioning
confidence: 99%
“…Glutamatergic neurons (Vglut2-expressing) in the VN have been proven susceptible to complex I 332 deficiency (Bolea et al, 2019). To define the factors driving this specific susceptibility, we first 333 confirmed the feasibility of the AAV-mitoTag approach for the isolation of mitochondria from this 334 genetically defined neuronal population in vivo.…”
Section: Cell Type-specific Isolation Of Mitochondria From Glutamatermentioning
confidence: 94%
“…NDUFS4 deficiency reveals a cell type-specific susceptibility to the disease. NDUFS4 ablation in 60 glutamatergic neurons (Vglut2-expressing) recapitulates most of the phenotype present in the global 61 NDUFS4-deficient mice (Bolea et al, 2019), thus warranting further study of glutamatergic neurons 62 in the VN. 63…”
Section: Introduction 38mentioning
confidence: 94%